A Campus Education Model for Department Chairs Councils - Christopher Barrick (Academic Chairpersons Conference Proceedings, 2018)
This presentation examines common missions for department chairs councils and proposes a framework that serves its members by offering campus-specific education. In this model, department chairs learn the ins and outs of their campus, including operations, meeting key university leaders, understanding available resources, and new developments across campus.
Keywords: council; network; chairs; chairpersons; academic chairs